2017
DOI: 10.1001/jamasurg.2017.1087
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adjuvant Chemotherapy With Survival in Patients With Stage II or III Gastric Cancer

Abstract: The survival prediction model can be used to make individualized predictions of the expected survival benefit from the addition of adjuvant chemotherapy for patients with stage II or stage III gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
131
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 36 publications
(67 reference statements)
5
131
0
Order By: Relevance
“…In addition, aging is accompanied by many physiological changes including those in the immune system and elder patients have weaker immune function in contrast with younger individuals [16][17][18]. Several studies supported that there are age-dependent variations on cancer immune surveillance, including degenerative changes of lymph nodes and reduced lymphatic flow to nodes and nodal involution [16,[19][20][21]. These data suggest that GC in younger patients may behave biologically more aggressively than in older patients and fit with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, aging is accompanied by many physiological changes including those in the immune system and elder patients have weaker immune function in contrast with younger individuals [16][17][18]. Several studies supported that there are age-dependent variations on cancer immune surveillance, including degenerative changes of lymph nodes and reduced lymphatic flow to nodes and nodal involution [16,[19][20][21]. These data suggest that GC in younger patients may behave biologically more aggressively than in older patients and fit with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, accurate prediction of lymph node involvement is essential in helping doctors make decisions more reasonably [20,[25][26][27][28][29]. Treatment recommendations for a patient with GC would vary depending on lymph node status.…”
Section: Discussionmentioning
confidence: 99%
“…(10,17,19) Furthermore, a survival prediction model based on specific tumor and patient clinicopathologic characteristics could be used to predict survival benefit from adjuvant chemotherapy for patients with stage II or stage III GC. (20) On the basis of these findings, we hypothesize that combining multiple clinicopathologic features and immunomarkers of immune cells and angiogenesis in tumor can improve overall prediction of GC outcome.…”
Section: Introductionmentioning
confidence: 93%
“…The most extensive study in the prediction model derived from the CLASSIC study, which includes 746 patients in the discovery set and 943 in the validation set. However, it is only a survival predicting model with clinical variables (30). In the present study, we demonstrated a prediction model based on metabolic genes of chemo-reagents and clinic-pathological variables with high accuracy in the prediction of chemotherapy e cacy in two independent cohorts of LAGC patients.…”
Section: C-score Is An Ideal Predictor For Adjuvant Therapy E Cacy Inmentioning
confidence: 67%